Redistribution of Histone Marks on Inflammatory Genes Associated With Intracerebral Hemorrhage-Induced Acute Brain Injury in Aging Rats - Zhang, Qin; Kong, Wei-lin; Yuan, Jun-Jie; Chen, Qiong; Gong, Chang-Xiong; Liu, Liang; Wang, Fa-Xiang; Huang, Jia-Cheng; Yang, Guo-Qiang; Zhou, Kai; Xu, Rui; Xiong, Xiao-Yi; et al. (Frontiers in Neuroscience, 2022)
The contribution of histone mark redistribution to the age-induced decline of endogenous neuroprotection remains unclear. In this study, we used an intracerebral hemorrhage (ICH)-induced acute brain injury rat model to study the transcriptional and chromatin responses in 13- and 22-month-old rats. Transcriptome analysis (RNA-seq) revealed that the expression of neuroinflammation-associated genes was systematically upregulated in ICH rat brains, irrespective of age. Further, we found that interferon-γ (IFN-γ) response genes were activated in both 13- and 22-month-old rats. Anti-IFN-γ treatment markedly reduced ICH-induced acute brain injury in 22-month-old rats. At the chromatin level, ICH induced the redistribution of histone modifications in the promoter regions, especially H3K4me3 and H3K27me3, in neuroinflammation-associated genes in 13- and 22-month-old rats, respectively. Moreover, ICH-induced histone mark redistribution and gene expression were found to be correlated. Collectively, these findings demonstrate that histone modifications related to gene expression are extensively regulated in 13- and 22-month-old rats and that anti-IFN-γ is effective for ICH treatment, highlighting the potential of developing therapies targeting histone modifications to cure age-related diseases, including brain injury and neuroinflammation.